2023
DOI: 10.1039/d3cp01821k
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear quantum and H/D isotope effects on intramolecular hydrogen bond in curcumin

Abstract: Low-barrier hydrogen bond in curcumin and hemicurcuminoids are studied. Path integral molecular dynamics simulations reveal that the correlation between the proton migration and the reorganization of the π-delocalized structure is not so strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Fast, reversible dislocation of the H atom along the O–O axis, however, should not completely scramble the OH stretch dipole orientation. Small fluctuations of the H/D atoms around the equilibrium position should likewise result in partial anisotropy decay. , While rapid fluctuations of the H/D atom positions certainly contribute to the early time orientational dynamics, they should not contribute to the longer time scales nor result in complete decay of the anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Fast, reversible dislocation of the H atom along the O–O axis, however, should not completely scramble the OH stretch dipole orientation. Small fluctuations of the H/D atoms around the equilibrium position should likewise result in partial anisotropy decay. , While rapid fluctuations of the H/D atom positions certainly contribute to the early time orientational dynamics, they should not contribute to the longer time scales nor result in complete decay of the anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several groups and we have reported that NQEs of hydrogen nuclei enhance the hydrogen bond strength and facilitate proton transfer reactions. 19–24 Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24…”
Section: Introductionmentioning
confidence: 90%
“…19–24 Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24…”
Section: Introductionmentioning
confidence: 90%